The Development of AR Books for Thematic Contents of Science and Social Studies in Elementary School to Foster Literacy and Numeracy Skills - Tetep; Ismail, Ali; Nasrulloh, Iman; Puspa, Adinda (Migration Letters, 2024)
The present study aimed to develop an AR book that focuses on fostering literacy and numeracy skills for elementary school students. We employed the ADDIE (Analysis, Design, Develop, Implement, and Evaluate) framework as a research design to develop an AR book. To examine several stages in ADDIE, we involved several groups of participants, all of whom were chosen using the purposive sampling technique, as their appropriateness aligned with our research goals: two professional fifth-grade elementary school teachers, three experts in educational technologies, and 20 sixth-grade elementary students. All of them contributed to the examination of AR books. Several analyses, including bibliometric analysis, portability tests, content validity index (CVI), and the System Usability Scale (SUS), were used to ensure that the AR book fulfills the requirements of the literacy and numeracy skills context in the Indonesian curriculum for elementary schools. Based on our measurements and data analysis, we revealed that the developed AR book had an appropriate framework, achieved a successful installation rate on several Android OS platforms, and was categorized “good” based on the System Usability Scale. This demonstrates that the AR book is ready to be applied in the classroom and has the potential to benefit the training of literacy and numeracy skills in elementary schools.